PMS2-associated Lynch syndrome: Past, present and future - Andini, Katarina D.; Nielsen, Maartje; Suerink, Manon; Helderman, Noah C.; Koornstra, Jan Jacob; Ahadova, Aysel; Kloor, Matthias; Mourits, Marian J.E.; Kok, Klaas; Sijmons, Rolf H.; Bajwa–ten Broeke, Sanne W. (Frontiers in Oncology, 2023)
Carriers of any pathogenic variant in one of the MMR genes (path_MMR carriers) were traditionally thought to be at comparable risk of developing a range of different malignancies, foremost colorectal cancer (CRC) and endometrial cancer. However, it is now widely accepted that their cancer risk and cancer spectrum range notably depending on which MMR gene is affected. Moreover, there is increasing evidence that the MMR gene affected also influences the molecular pathogenesis of Lynch syndrome CRC. Although substantial progress has been made over the past decade in understanding these differences, many questions remain unanswered, especially pertaining to path_PMS2 carriers. Recent findings show that, while the cancer risk is relatively low, PMS2-deficient CRCs tend to show more aggressive behaviour and have a worse prognosis than other MMR-deficient CRCs. This, together with lower intratumoral immune infiltration, suggests that PMS2-deficient CRCs might have more in common biologically with sporadic MMR-proficient CRCs than with other MMR-deficient CRCs. These findings could have important consequences for surveillance, chemoprevention and therapeutic strategies (e.g. vaccines). In this review we discuss the current knowledge, current (clinical) challenges and knowledge gaps that should be targeted by future studies.